Business Development Strategy Through The Business Model Canvas Approach of Omah Kopi Mandiri Tulungagung - Satriyono, Gandung; Meme, Meme; Vaulia, Nindi; Rizky, Edwina Prastiwi Sri; Agustina, Eka (Islamic University of Kalimantan MAB Banjarmasin, 2024)
This research explores the implementation of Business Model Canvas (BMC) in business development strategies at Omah Kopi Mandiri Tulungagung. BMC is used as the foundation for their business strategy, introducing local coffee variations to diverse markets. The purpose of this study is to evaluate the application of BMC by Omah Kopi Mandiri Tulungagung in the expansion and development of their local coffee business. The qualitative research approach is carried out through interviews, observation, and analysis of documents related to BMC. The results of the analysis show the successful implementation of BMC by Omah Kopi Mandiri Tulungagung by successfully reaching a wide market segment, using distribution channels through their Instagram platform and offline stores. The main revenue comes from the sale of coffee products with a focus on production, packaging, and marketing. Cooperation with local coffee farmers and raw material suppliers is an important factor in the company's operations. This study confirms the successful implementation of BMC as the foundation of business strategy, while recommending expansion of distribution channels and product innovation to achieve a wider market share for Omah Kopi Mandiri Tulungagung's local coffee business